1992
DOI: 10.1364/ol.17.000417
|View full text |Cite
|
Sign up to set email alerts
|

Soliton fiber ring laser

Abstract: A fiber ring laser that can produce nearly transform-limited soliton pulses is simulated. This laser has an erbium-doped optical-fiber amplifier and allows wavelength tuning through the interplay of fiber chromatic dispersion and the round-trip delay time of the laser. We show that a saturable absorber and a frequency limiter are required for the ring laser to self-start, i.e., to mode lock from initial noise and to operate stably. We also show that nonlinear polarization rotation with polarization selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(78 citation statements)
references
References 6 publications
3
75
0
Order By: Relevance
“…Mode-locking has been achieved using this technique in linear cavities with Nd +3 -doped fiber [27] and Er +3 -doped fiber [37], although these lasers required active modulators for pulse initiation. Simulations of a soliton fiber ring laser showed that a saturable absorber (nonlinear polarization rotation) and frequency limiter were required for the ring laser to self-start [38]. A self-starting ring cavity with low-birefringence fiber was then demonstrated at 1.55 µm, although the 1.2-ps soliton pulses were randomly spaced in bunches at the round-trip frequency [28].…”
Section: Review Of Passive Mode-locking Techniques and Resultsmentioning
confidence: 99%
“…Mode-locking has been achieved using this technique in linear cavities with Nd +3 -doped fiber [27] and Er +3 -doped fiber [37], although these lasers required active modulators for pulse initiation. Simulations of a soliton fiber ring laser showed that a saturable absorber (nonlinear polarization rotation) and frequency limiter were required for the ring laser to self-start [38]. A self-starting ring cavity with low-birefringence fiber was then demonstrated at 1.55 µm, although the 1.2-ps soliton pulses were randomly spaced in bunches at the round-trip frequency [28].…”
Section: Review Of Passive Mode-locking Techniques and Resultsmentioning
confidence: 99%
“…Mode locking of the laser was achieved by using the effect of non-linear rotation of radiation polarisation (C.J. Chen et al, 1992;Matsas et al, 1992;Chong et al, 2008). Control over the polarisation was carried out with the help of three phase plates inserted into the laser cavity.…”
Section: Review Of Recent Progress In Mode-locked Fibre Lasers With Hmentioning
confidence: 99%
“…The latter is further related to the laser gain. Chen et al have analytically derived the cavity transmission of such lasers [19]. With a fixed linear light polarization rotation bias, the actual cavity transmission is a sinusoidal function of the nonlinear light polarization rotation.…”
Section: Mechanism Of Pulse Nonuniformitymentioning
confidence: 99%